Mendorong Perilaku Ramah Lingkungan di Kalangan Wisatawan Melalui Pengalaman Lingkungan dan Ikatan Terhadap Tempat dengan Memperkuat Kepedulian Lingkungan dalam Pariwisata Alam di Nusa Tenggara Barat - Pandu Sapto Desmantyo; Rochmah Dewi Suryani; Rivaldi Arissaputra; Sarah Sentika (Fakultas Ekonomi Universitas Garut, 2026)
The growth of nature-based tourism in Indonesia has not been accompanied by a corresponding improvement in visitor environmental behaviour, creating a persistent gap between tourism expansion and ecological sustainability. This study examines the relationships among Experiencescape, Place Attachment, Environmental Concern, and Environmentally Responsible Behaviour (ERB) among tourists visiting nature-based destinations in Nusa Tenggara Barat (NTB), Indonesia. Using a quantitative verificative design, data were collected from 266 respondents through purposive sampling and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with 5,000 bootstrapping resamples. The results confirm that Experiencescape significantly influences Place Attachment, and that Place Attachment positively drives ERB. However, Experiencescape did not directly influence ERB, indicating that behavioural change operates through emotional mediation rather than direct experiential stimuli. Environmental Concern significantly moderated the Experiencescape–Place Attachment relationship in a negative direction, suggesting that environmentally conscious visitors apply more critical evaluative standards to the experiential environment. Environmental Concern did not significantly moderate either the Experiencescape–ERB or Place Attachment–ERB relationships. These findings highlight that fostering deep emotional bonds between tourists and natural destinations is more effective than relying on experiential quality alone to promote responsible environmental behaviour. Destination managers and policymakers in NTB are encouraged to prioritise ecologically authentic and interpretive experiencescape designs that strengthen place attachment as an indirect pathway to sustainable visitor conduct.